Improving Secondary School Mathematics Teachers’ Effective Lesson Implementation through Lesson Study - Temesgen Yadeta Dibaba; Abbi Lemma Wedajo; Faith Maina; Adula Bekele Hunde (IAFOR Journal of Education)
The main purpose of this study was to explore how engaging in lesson study improves secondary mathematics teachers’ effective lesson implementation to support students’ learning better. The research was conducted in Jimma City, Ethiopia, and employed design-based research with qualitative data collected from two secondary schools and 12 mathematics teachers. A purposive sampling technique was used to select participants. Interviews, observations, and document analysis were the main sources of data. The data were analyzed thematically supported by Atlas-ti qualitative data analysis software. Findings indicated that engaging in lesson study improved mathematics teachers’ effective lesson implementation. LS improved participants’ practice of lesson presentation, use of diverse student-centered teaching methods, assessment, behavior management, instructional aids, time management, and feedback strategies. School leaders’ positive attitudes and teachers’ commitment were found to be supportive, while shortage of time and teachers’ high teaching load were constraints. It would be vital to integrate lesson study into teachers’ school-based professional development programs to improve mathematics teachers’ effective lesson implementation in the study setting. The study suggests further investigation in more secondary schools by incorporating quantitative evidence with larger a sample size.